Price Floors and Employer Preferences: Evidence from a Minimum Wage Experiment - Horton, John J. (American Economic Review, 2025)
Firms posting job openings in an online labor market were randomly assigned minimum hourly wages. When facing a minimum wage, fewer firms hired, but those they did hire paid higher wages. Hoursworked fell substantially. Treated firms shifted to hiring more productive workers. Using the platform's imposition of a market-wide minimum wage after the experiment, I find that many of the experimental results also hold in equilibrium, including the substitution towards more productive workers. However, there was also a large reduction in the number of jobs posted for which the minimum wage would likely bind. (JEL J22, J23, J31, J38)